The effect of processing pork carcasses prior to rigor mortis upon muscle and fat quality - Weiner, P.D.; Kropf, Donald H.; Mackintosh, D.L.; Koch, B.A. (Kansas Agricultural Experiment Station, 2011)
The effect of processing pork carcasses before rigor mortis was studied in 21 market-weight swine. The left side of each carcass served as a control and was chilled for 48 hours at 32-36 F before being cut and processed by regular methods. The right sides (treated) were cut and processed within one hour of bleeding.
Keywords: Pork; Muscle quality; Fat quality; Rigor mortis